The Relationships among Classroom Management, Work Culture, and Pedagogical Competence among Islamic High School Teachers - Moch. Abdul Rohman; Ruhiat, Yayat; Atikah, Cucu (Universitas Islam Negeri Raden Fatah Palembang, South Sumatra, Indonesia, 2025)
This study was aimed to analyze the relationship between classroom management, teacher work culture, and pedagogical competence among Islamic high school teachers in Cikande District, Serang Regency. The research was conducted in four schools, with a total sample of sixty-nine teachers. Data were collected using closed questionnaires based on a Likert scale, which had been validated through a t-test. The collected data were analyzed using inferential statistics with a correlational approach, employing SPSS version 23 software. The results of this study indicated that classroom management had a significant relationship with pedagogical competence; specifically, classroom management was directly related to pedagogical competence. In contrast, teacher work culture exhibited a weaker relationship with pedagogical competence. The Pearson Correlation Value was 0.683 for classroom management and 0.774 for teacher work culture. The R value of 0.793 indicated a strong relationship between classroom management, teacher work culture and pedagogical competence. This finding proved that classroom management had a central role in improving pedagogical competence and creating a good work culture.